New Zealand’s Waitangi Day divided? Support for national Day predicts in-group and out-group warmth for Pākehā but only in-group warmth for Māori - Matika, Correna M.; Houkamau, Carla A.; Sibley, Chris G. (International Journal of Intercultural Relations, 2021)
Waitangi Day, New Zealand’s official national day, is often claimed as contentious by commentators and academics. However, research analysing the wider population’s opinions about Waitangi Day are lacking. We address this with two studies using national probability data from the New Zealand Attitudes and Values Study. Most participants supported (51%), rather than opposed (8%), Waitangi Day as a national celebration of biculturalism. Study one indicated that, on average, Pākehā (N = 12390) who opposed Waitangi Day as a bicultural celebration expressed warmer attitudes towards Pākehā but colder attitudes towards Māori. Conversely, support for Waitangi Day as a bicultural celebration among Māori (N = 1928) was, on average, related to warmth towards Māori but uncorrelated with warmth towards Pākehā. Study two assessed whether socio-political attitudes changed in the weeks leading up to, during, and immediately following Waitangi Day in 2015. Contrary to narratives of divisiveness, we failed to detect reliable change in the attitudes of Māori (N = 556) and Pākehā (N = 3203) around Waitangi Day. These findings are inconsistent with anecdotal claims that Waitangi Day may be divisive.
Keywords: Waitangi Day; commemoration; national day; tiriti o waitangi/treaty of waitangi

Region-level Pākehā warmth towards Māori enhances collective action intentions: An extension of the social identity model of collective action (SIMCA) - Houkamau, Carla; Bahamondes, Joaquín; Osborne, Danny; Sibley, Chris (International Journal of Intercultural Relations, 2024)
New Zealand is a peaceful nation, but ongoing political tensions and inequities between Māori (the indigenous peoples of New Zealand) and Pākehā (the majority group of Europeans) persist as a result of its colonial history. Identifying ways to redress the enduring legacy of colonialism are therefore of critical importance. Accordingly, this paper examines data from 7017 Māori, as well as 37,233 Pākehā, to examine the impact of regional-level Pākehā warmth towards Māori on Māori support for progressive collective action. Results reveal that Pākehā warmth towards Māori varies markedly across 257 regional wards (regional units created for New Zealand electoral purposes). Moreover, multilevel modelling demonstrates that Pākehā warmth towards Māori at the region-level correlates positively with Māori identity and political efficacy at the individual level which, in turn, both correlate positively with collective action support. Collectively, these results demonstrate the impact of the broader social climate on social change, while identifying a previously-unknown facilitator of collective action support (namely, a broader context of warmth towards structurally disadvantaged groups).
Keywords: Activism; Māori; Political rights; Social identity model of collective action (SIMCA)

Exploring the relationship between support for protest and psychological well-being for Māori - Houkamau, Carla A; Stronge, Samantha; Osborne, Danny; Sibley, Chris G; Dell, Kiri (New Zealand Journal of Psychology, 2020)
As a colonised peoples, many Māori have engaged in various forms of political resistance. Accordingly, research suggests that socio-political consciousness, which will sometimes involve at least considering protest, is an increasingly important aspect of identifying as Māori. This paper draws on a large, nationally representative sample of Māori (N = 1,977) to examine the links between expressing support for political activism (“activism” being used here synonymously with “protest”) and well-being. Support for political activism includes merely contemplating protesting and voting to support Māori issues, as well as actually signing petitions. Well-being includes selfreported mental health via the Kessler-6 and subjective health. Results show that support for political activism was strongly associated with greater subjective psychological distress and lower subjective health, above and beyond the variance explained by exhaustive demographic factors. This research presents the first empirical data in New Zealand demonstrating the strength of this relationship, and provides a good starting point for further investigation.
Keywords: activism; protest